Death in the Mouth: The Current Status of Pesticide Residues in Cured Fish from Selected Markets in Rivers State Nigeria - R.B, Bob-Manuel; E, Egbecho; U, Zakka (International Research Journal of Insect Sciences, 2020)
Pesticide residues in cured fish from selected markets in Rivers State, Nigeria were determined to compare their residues content with FAO/WHO MRLs. The research was carried out at Ignatius Ajuru University of Education and Austino Research Laboratories, Rivers State, Nigeria. Samples of cured fish were collected from different major markets in Rivers State, Nigeria. Each product was purchased from three different traders and kept in an air tight Ziploc envelope containing general information. Some of the samples were kept in 250 g plastic containers and kept on a laboratory bench for a period of 45 days to observe insect emergence while the other lots were taken to Austino Research Laboratory for pesticide residue analysis. The result shows varying degrees of damage ranging from slightly to undamaged and mean number of D. maculatus emergence was higher in smoked fish samples obtained at Rumuokwuta. The result also shows that in all the cured fish sampled, DDT, Captan, Hexazinone, and Tecnazene were found above the FAO/WHO MRLs and few compounds were below the MRLs. Conclusively, relevant authorities and agencies needs to increase surveillance and monitoring to check and control the illegal importation, sale and use of such compounds especially in controlling stored pests of cured fish. This could reduce cases of pesticide toxicity and food poisoning and other health implications due to its ingestion in such contaminated cured fish.